THE ROLE OF A TEACHER IN POPULAR CULTURAL ACTION - Sarmiento Moreno, Luis Abrahán (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Popular Cultural Action (PCA) is an educational experience that brings school to households and other marginalized groups, involving family and community. This dynamic relationship: school, family and society, coupled and combined with the systematic use, technologies and social mass media produces as a result important insights for the development of  humanity: education, education for life, open education, distance education, education for all, mediated teaching, independent learning and participatory education. This perception implies to replace a single and closed curriculum for programs that respond to the reality and pay attention to participants’ social interests; to change student’s anxiety into another purpose in which the student is treated as responsible for his own learning. The teacher assumes a cooperative role  to accompany the learner’s integral development achievement. A new pedagogical fact is possible inasmuch as renewed agents are involved in the processes. Hence a question arises: What is the teacher’s role in Popular Cultural Action? To answer this question, broad reading of primary and secondary sources has been done and discussion with people involved in the educational process has been carried out as well.